IMPLEMENTATION AND COMPARISON OF SOFTWARE-DEFINED NETWORK CONTROLLERS IN VARIOUS SIMULATED NETWORK ENVIRONMENTS (FUDMA JOURNAL OF SCIENCES, 2025)
In today's ever-evolving networking landscape, Software Defined Networking (SDN) has emerged as a paradigm-shifting technology that promises greater flexibility, agility, and control over network infrastructures. However, how easy are the configuration, extensibility, and programmability of these SDN controllers, considering the practical implications for network administrators and developers? Despite the growing adoption of SDN, there is limited research on the comparative performance of controllers across multiple simulation environments. This study aims to explore the practical implementation and comparative evaluation of different SDN Controllers within diverse simulated network environments. Prominent controllers such as POX and Faucet are meticulously configured and deployed in simulated network environments created using GNS3 (Graphical Network Simulator-3), OPNET (Optimized Network Engineering Tools), NS3 (Network Simulator-3), OMNET++ (Objective Modular Network Testbed in C++) and MININET platforms. Furthermore. the study employs a range of performance metrics like controller latency, network throughput, packet loss, CPU (Central Processing Unit) and memory utilization to assess the efficacy and efficiency of each SDN Controller. The Results indicated that Mininet provided the lowest latency, whereas OPNET demonstrated better scalability for large-scale networks. NS3, though useful for SDN network design and visualization, exhibited higher CPU and memory utilization that might limit its scalability for large-scale SDN controller simulations. While GNS3 offered a balanced performance and resource utilization, making it a suitable choice for SDN controller simulation that prioritizes realistic network modelling, OMNET++, on the other hand, exhibited moderate performance metrics with efficient resource utilization, making it suitable for SDN controller simulations requiring a balance between performance...
Keywords: SDN Controller; POX; FAUCET; Network Simulator; Performance Metrics; OpenFlow